Paraquat Poisoning In Children – A Case Report - Shah, Syed Sajid Hussain; Aalia, Bibi (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES Accidental poisoning in children is a serious public health problem in developing countries, especially where chemicals used in agriculture are ingested. Paraquat is a herbicide which is still used in Pakistan. We report a case of fatal unintentional paraquat ingestion by 3 years old child who could not survive. Lack of care in the storage of paraquat lead to the poisoning but initial inappropriate management was also one factor in the fatal outcome. Detailed history and provision of poison containers are important in the proper management of patients with poisoning.